Combining Reaction Time and Accuracy: The Relationship Between Working Memory Capacity and Task Switching as a Case Example - Draheim, Christopher; Hicks, Kenny L.; Engle, Randall W. (Perspectives on psychological science, 2016)
It is generally agreed upon that the mechanisms underlying task switching heavily depend on working memory, yet numerous studies have failed to show a strong relationship between working memory capacity (WMC) and task-switching ability. We argue that this relationship does indeed exist but that the dependent variable used to measure task switching is problematic. To support our claim, we reanalyzed data from two studies with a new scoring procedure that combines reaction time (RT) and accuracy into a single score. The reanalysis revealed a strong relationship between task switching and WMC that was not present when RT-based switch costs were used as the dependent variable. We discuss the theoretical implications of this finding along with the potential uses and limitations of the scoring procedure we used. More broadly, we emphasize the importance of using measures that incorporate speed and accuracy in other areas of research, particularly in comparisons of subjects differing in cognitive and developmental levels.